Evolved Gas Analyses of Sedimentary Rocks From the Glen Torridon Clay‐Bearing Unit, Gale Crater, Mars: Results From the Mars Science Laboratory Sample Analysis at Mars Instrument Suite. Issue 9 (26th September 2022) - McAdam, A. C.; Sutter, B.; Archer, P. D.; Franz, H. B.; Wong, G. M.; Lewis, J. M. T.; Clark, J. V.; Millan, M.; Williams, A. J.; Eigenbrode, J. L.; Knudson, C. A.; Freissinet, C.; et al.
Abstract: Evolved gas analysis (EGA) data from the Sample Analysis at Mars (SAM) instrument suite indicated Fe‐rich smectite, carbonate, oxidized organics, Fe/Mg sulfate, and chloride in sedimentary rocks from the Glen Torridon (GT) region of Gale crater that displayed phyllosilicate spectral signatures from orbit. SAM evolved H2 O data indicated that the primary phyllosilicate in all GT samples was an Fe‐rich dioctahedral smectite (e.g., nontronite) with lesser amounts of a phyllosilicate such as mixed layer talc‐serpentine or greenalite‐minnesotaite. CO2 data supported the identification of siderite in several samples, and CO2 and CO data was also consistent with trace oxidized organic compounds such as oxalate salts. SO2 data indicated trace and/or amorphous Fe sulfates in all samples and one sample may contain Fe sulfides. SO2 data points to significant Mg sulfates in two samples, and lesser amounts in several other samples. A lack of evolved O2 indicated the absence of oxychlorine salts and Mn 3+ /Mn 4+ oxides. The lack of, or very minor, evolved NO revealed absent or very trace nitrate/nitrite salts. HCl data suggested chloride salts in GT samples. Constraints from EGA data on mineralogy and chemistry indicated that the environmental history of GT involved alteration with fluids of variable redox potential, chemistry and pH under a range of fluid‐to‐rock ratio conditions. Several of the fluid episodes could have provided habitable environmental conditions and carbon would have been available to any past microbes though the lack of significant N could have been a limiting factor for microbial habitability in the GT region. Plain Language Summary: The Mars Science Laboratory Curiosity rover carried out a comprehensive investigation of the sedimentary rocks in the Glen Torridon (GT) region in Gale crater, Mars, to better understand Martian geologic history. The rover's Sample Analysis at Mars instrument suite was used to heat samples from GT and detect gases that were evolved to help identify the volatile‐bearing mineralogy of the samples. Results indicated the presence of Fe‐rich smectite, carbonate, oxidized organics, Fe and Mg sulfate, and chloride while oxychlorine salts, Mn 3+ /Mn 4+ oxides, and nitrate/nitrite salts were either not detected or occurred in trace amounts. This mineralogy data implied that geochemical conditions and fluid‐to‐rock ratios varied over time and that the conditions of GT depositional and diagenetic environments would have been amenable to microbial life with sufficient carbon but nitrogen abundances could have been limiting. Key Points: Sample Analysis at Mars data indicated Fe‐smectite, carbonate, oxidized organics, Fe/Mg sulfates, and chlorides in Glen Torridon (GT) rocks GT's environmental history involved fluids of variable redox potential and chemistry under a range of fluid‐to‐rock ratios Fluid episodes could have provided habitable environments and carbon was present, but nitrogen could have been a limiting factor